Liberia : Seventh and Eighth Reviews Under the Extended Credit Facility Arrangement, and Request for Nonobservance of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Liberia. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Liberia's Seventh and Eighth Reviews under the Extended Credit Facility Arrangement, and Request for Waiver of Nonobservance of Performance Criteria (PCs). Three of six structural benchmarks (SBs) for the seventh review and two of four SBs for the eighth review were met. The rest, except one, were met with a delay. Risks are concentrated in the near term. Based on the strength of the authorities' policy commitments and corrective measures, the IMF staff supports the authorities' request for waivers for nonobservance of PCs and supports completion of the seventh and eighth program reviews.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet